Modeling the pump down of a reversibly adsorbed phase in complex vacuum systems. (August 2017) - Urbano, M.F.; Manini, P.
Highlights: Numerical approach addressing the pump down of reversibly adsorbed phase (e.g. water) in complex vacuum system. Mathematical model based on the view factor (or angular coefficients) methods coupled with the Langmuir adsorption desorption kinetic model. Model tested on a spherical vacuum system and results are compared to the ones obtained with the well-known Redhead model. Model applied to a more complex vacuum system in order to appreciate the effect of pressure inhomogeneity.